Cenozoic extension in the Kenya Rift from low‐temperature thermochronology: Links to diachronous spatiotemporal evolution of rifting in East Africa. Issue 12 (1st December 2015) - Torres Acosta, Verónica; Bande, Alejandro; Sobel, Edward R.; Parra, Mauricio; Schildgen, Taylor F.; Stuart, Finlay; Strecker, Manfred R.
Abstract: The cooling history of rift shoulders and the subsidence history of rift basins are cornerstones for reconstructing the morphotectonic evolution of extensional geodynamic provinces, assessing their role in paleoenvironmental changes and evaluating the resource potential of their basin fills. Our apatite fission track and zircon (U‐Th)/He data from the Samburu Hills and the Elgeyo Escarpment in the northern and central sectors of the Kenya Rift indicate a broadly consistent thermal evolution of both regions. Results of thermal modeling support a three‐phased thermal history since the early Paleocene. The first phase (~65–50 Ma) was characterized by rapid cooling of the rift shoulders and may be coeval with faulting and sedimentation in the Anza Rift basin, now located in the subsurface of the Turkana depression and areas to the east in northern Kenya. In the second phase, very slow cooling or slight reheating occurred between ~45 and 15 Ma as a result of either stable surface conditions, very slow exhumation, or subsidence. The third phase comprised renewed rapid cooling starting at ~15 Ma. This final cooling represents the most recent stage of rifting, which followed widespread flood‐phonolite emplacement and has shaped the present‐day landscape through rift shoulder uplift, faulting, basin filling, protracted volcanism, and erosion. When compared with thermochronologic and geologic data from other sectors of the East African Rift System, extension appears to be diachronous, spatially disparate, and partly overlapping, likely driven by interactions between mantle‐driven processes and crustal heterogeneities, rather than the previously suggested north–south migrating influence of a mantle plume. Key Points: Data and modeling show Paleogene and middle Miocene cooling episodes Cooling episodes separated by stable conditions, slow exhumation, or subsidence Extension pattern is compatible with random rift initiation above a plume